Profils du concept de Pologne dans la revue Polska en 1968. Étude des textes de propagande extérieure à destination des lecteurs du premier, du second et du tiers monde - Solová, Regina (Studia Romanica Posnaniensia, 2023)
This paper examines the profiles of the concept of Poland based on a corpus of foreign propaganda texts published in French and Slovak in 1968. The texts analysed come from three magazines: La Pologne, Polsko and La Revue Polonaise, created by political decision of the communist leaders to disseminate a positive image of Poland abroad. The purpose of this study is to test the hypothesis that the three profiles of the concept of Poland, aimed at first, second and third-world audiences, are different from each other due to differences motivated by extra-linguistic factors, and in particular, the various objectives of the country’s foreign policy. The study is inspired by the work of the Lublin School of Ethnolinguistics on the linguistic representation of reality. Its methods make it possible to identify variants of the representation of an object through the examination of textual data, such as the ways of naming it, the semantic relations of synonymy and antonymy, or the series of its aspects mobilised in the discourse.